OPTIMIZATION OF PREMEDICATION IN SURGICAL INTERVENTION IN GYNECOLOGY PRACTICE - Khudoyberdieva Gulrukh Sobirjonovna (Journals Park Publishing, 2024)
The article is devoted to the study of the effectiveness of the drug etifoxine (strezam) in complex premedication in gynecological patients against the background of pathological menopause syndrome. The use of stresam as a therapeutic premedication in patients with pathological climacteric syndrome has shown an increase in the level of medical and social rehabilitation and a reduction in the length of hospital stay of patients.
Keywords: treatment, premedication, etifoxine, anxiety-depressive disorders, pathological menopause syndrome, gynecology.